Variation in referral practice for patients with colorectal cancer liver metastases. Issue 12 (9th October 2013) - Young, A. L.; Adair, R.; Culverwell, A.; Guthrie, J. A.; Botterill, I. D.; Toogood, G. J.; Lodge, J. P. A.; Prasad, K. R.
<x xml:space="preserve">Abstract</x> Background Half of patients with colorectal cancer develop liver metastases. There remains great variability between hospitals in rates of liver resection for colorectal cancer liver metastases (CLM). This study aimed to determine how many patients with potentially resectable CLM are not seen by specialist liver surgeons. Methods Patients presenting with new CLM in a cancer network consisting of a tertiary centre and seven attached hospitals were studied prospectively over 12 months. Data were collected retrospectively for patients who did not have a complete data set. Outcomes for patients referred to the liver tertiary centre were collated. The radiology of tumours deemed inoperable by the local colorectal specialist teams was reviewed by specialist liver surgeons and radiologists. Results In total, 631 patients with CLM were assessed. Prospective data were complete for 241 patients, and 64 (26·6 per cent) of these were referred to the specialist liver team for consideration of resection. No decision was documented for 16 patients (6·6 per cent). Of those not referred, 30 (18·6 per cent) were deemed unfit or refused and 131 (81·4 per cent) were thought inoperable. Referral rates varied between hospitals (13–43·6 per cent). Of 131 patients deemed fit but inoperable by the colorectal specialist teams, 38 (29·0 per cent) were deemed operable and 20 (15·3 per cent) had equivocal imaging when assessed retrospectively by liver specialists. In total, 142 of the 631 patients were referred to liver specialists for consideration of treatments, and 107 (75·4 per cent) treated with curative intent. Conclusion A considerable number of patients with potentially resectable CLM are not assessed by specialist liver teams. Improved referral rates could greatly improve resection rates for CLM, which may improve outcomes for patients with colorectal cancer.